Hubungan Citra Tubuh, Aktivitas Fisik dan Pengetahuan Gizi dengan Status Gizi Remaja Putri di SMAN 1 Wawonii Barat - Yansah, Deri; Dhesa, Desiderius Bella; Ihsan, Habib; Abadi, Ellyani Abadi,; Ananda, Siti Hadrayanti (Sekolah Tinggi Ilmu Kesehatan Karya Kesehatan, 2025)
This research is an observational study using a cross-sectional study. The research population was 132 female students (adolescent girls) in class X and XI at SMAN 1 Wawonii Barat aged 15-17 years. The sample was taken as many as 57 people using proportional stratified random sampling. Data was collected through interviews using questionnaires and assessing nutritional status through measuring body weight and height. The data collected were the characteristics of young women, nutritional status based on BMI, body image, physical activity and respondents' knowledge about nutrition. Based on the research results, it was found that 61.4% of young women had thin nutritional status, 38.6% had dissatisfied body image, 47.4% had poor physical activity, 29.8% had poor nutritional knowledge. Statistical tests show that there is a significant relationship between physical activity (P=0.006) and nutritional knowledge (P=0.026) with the nutritional status of adolescent girls at SMAN 1 Wawonii Barat. In order to build a good body condition and resistance to disease, it is desired that students who now have poor nutritional status will attempt to improve it by adopting a balanced diet and taking regular pauses. Given that many pupils still have poor nutritional status, educators might use the research's findings as study material to shed light on the science of nutrition